Diversity of soil ciliates at oil palm plantation in Sungai Asap, Sarawak, Malaysia - Lee, Ting Ting (2015)
Palm oil industry is continuously making significant contribution to Malaysia’s economy and oil palm cultivation area is expanding especially in Sarawak. Thus research on the condition of plantation soil is needed to ensure its sustainability. In this research, soil ciliates (Protozoa: Ciliophora) was studied because they are potential bioindicators soil health and quality. Soil ciliates diversity at oil palm plantation and two secondary forests (biodiversity strip 1 and biodiversity strip 2) were studied using the semi-nested polymerase chain reaction reaction-denaturing gradient gel electrophoresis (PCR-DGGE) approach targeting for the small subunit ribosomal DNA (18S rDNA). A total of 480 soil samples were collected from December 2010 to July 2012. Microorganisms total DNA was extracted from all soil samples and ciliate 18S rDNA was amplified in semi-nested PCR using primer pairs EukA/CilDGGE-r and GC-CilF/CilDGGE-r. Amplified sequences were separated on polyacrylamide gel using DGGE approach. A total of 290 predominant DGGE bands were excised and subjected to sequencing. These sequences matched with ciliates in NCBI GenBank database with similarity between 91% to 100%. Phylogenetic analysis revealed 73 species which affiliated to seven classes, 17 orders, 27 families and 34 genera. Classes Spirotrichea, Litostomatea and Colpodea were the top three dominant groups followed by Oligohymenophorea, Nassophorea, Armophorea and Heterotrichea. Four ciliate classes were found in biodiversity strip 1 while six classes were found in both biodiversity strip 2 and oil palm plantation. Statistical analyses revealed that community structure and diversity of soil ciliates in three study sites showed spatial and temporal variations. Community structure of soil ciliates in plantation was more similar to biodiversity strip 2 than biodiversity strip 1. Meanwhile, the diversity indices in the plantation were moderately diverse as compared to biodiversity strips 1 and 2. Moreover, the diversity indices among the sites were statistically indistinguishable after two years of study. There was no obvious correlation of the spatio-temporal changes of soil ciliate diversity indices with the environmental variables studied herein. Only Simpson index of soil ciliates diversity at plantation was significantly negatively correlated to rainfall. This research provides an overview of the composition, diversity and community structures of soil ciliates at oil palm plantation and forests in Sungai Asap, Sarawak. These have resulted in an increased knowledge of the diversity of soil ciliates and are then expected leading towards knowing the soil quality especially at oil palm plantation and provide valuable knowledge for the development of sustainable oil palm plantation management.